Regulation of glycine metabolism by the glycine cleavage system and conjugation pathway in mouse models of non‐ketotic hyperglycinemia. Issue 6 (11th August 2020) - Leung, Kit‐Yi; De Castro, Sandra C. P.; Santos, Chloe; Savery, Dawn; Prunty, Helen; Gold‐Diaz, Diana; Bennett, Stuart; Heales, Simon; Copp, Andrew J.; Greene, Nicholas D. E.
Abstract: Glycine abundance is modulated in a tissue‐specific manner by use in biosynthetic reactions, catabolism by the glycine cleavage system (GCS), and excretion via glycine conjugation. Dysregulation of glycine metabolism is associated with multiple disorders including epilepsy, developmental delay, and birth defects. Mutation of the GCS component glycine decarboxylase (GLDC) in non‐ketotic hyperglycinemia (NKH) causes accumulation of glycine in body fluids, but there is a gap in our knowledge regarding the effects on glycine metabolism in tissues. Here, we analysed mice carrying mutations in Gldc that result in severe or mild elevations of plasma glycine and model NKH. Liver of Gldc‐deficient mice accumulated glycine and numerous glycine derivatives, including multiple acylglycines, indicating increased flux through reactions mediated by enzymes including glycine‐ N ‐acyltransferase and arginine: glycine amidinotransferase. Levels of dysregulated metabolites increased with age and were normalised by liver‐specific rescue of Gldc expression. Brain tissue exhibited increased abundance of glycine, as well as derivatives including guanidinoacetate, which may itself be epileptogenic. Elevation of brain tissue glycine occurred even in the presence of only mildly elevated plasma glycine in mice carrying a missense allele of Gldc . Treatment with benzoate enhanced hepatic glycine conjugation thereby lowering plasma and tissue glycine. Moreover, administration of a glycine conjugation pathway intermediate, cinnamate, similarly achieved normalisation of liver glycine derivatives and circulating glycine. Although exogenous benzoate and cinnamate impact glycine levels via activity of glycine‐ N ‐acyltransferase, that is not expressed in brain, they are sufficient to lower levels of glycine and derivatives in brain tissue of treated Gldc‐deficient mice.